2020
DOI: 10.1021/acsapm.9b00921
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Peptide–Polymer Conjugates for Dentistry

Abstract: Bacterial adhesion and growth at the composite/adhesive/tooth interface remain the primary cause of dental composite restoration failure. Early colonizers, including Streptococcus mutans, play a critical role in the formation of dental caries by creating an environment that reduces the adhesive's integrity. Subsequently, other bacterial species, biofilm formation, and lactic acid from S. mutans demineralize the adjoining tooth. Because of their broad spectrum of antibacterial activity and low risk for antibiot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
57
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(57 citation statements)
references
References 108 publications
0
57
0
Order By: Relevance
“…The co-polymerizable peptide was lyophilized, and stored at −20 • C. Crude peptides were also cleaved from the resin and then purified. The purified peptide fractions were combined and lyophilized (Xie et al, 2020).…”
Section: Co-polymerizable Hydroxyapatite-binding Peptidementioning
confidence: 99%
“…The co-polymerizable peptide was lyophilized, and stored at −20 • C. Crude peptides were also cleaved from the resin and then purified. The purified peptide fractions were combined and lyophilized (Xie et al, 2020).…”
Section: Co-polymerizable Hydroxyapatite-binding Peptidementioning
confidence: 99%
“…124 An alternative approach is the conjugation of AMPs with methacrylates to render them photopolymerizable for incorporation into dental resins. This approach 125,126 has been performed with GH12 (designed de novo 127 ) and shown to imbue the resins with antimicrobial activity while not affecting bulk mechanical properties. Another group has also incorporated an AMP derived from b defensin-3, a commonly used AMP detailed later, into an adhesive and showed disruption of S. mutans biofilms.…”
Section: Dental Restorative Materials Modification With Ampsmentioning
confidence: 99%
“…The above discussion revealed that antimicrobial peptides are promising for the development of peptide-based novel therapeutics and an alternative to conventional antibiotics. [55][56][57] Moreover, antimicrobial peptides have got much attention to overcome the drug resistance due to their unique mechanism of interaction with the target pathogens. However, various factors such as selectivity, cytotoxicity, side effects, drug resistance, etc.…”
Section: Therapeutic Perspectives Of Antimicrobial Peptidesmentioning
confidence: 99%